Pemanfaatan Ekstrak Kulit Bawang Merah (Allium Cepa L.) Sebagai Sediaan Lip Balm - Tutik, Tutik; Umri, Ulfa Nafila; Amalia, Putri (Jurnal Ilmiah Wahana Pendidikan, 2024)
Shallot skin (Allium cepa L.) is a market waste that can be used by the public for treatment which has potential as an antioxidant, namely flavonoids which can prevent the development of free radicals in the body. This study aims to make formulations in lip balm preparations using shallot skin extract and find out the best concentration in lip balm preparations. The research was carried out experimentally, including the formulation of lip balm preparations of various shallot skin extracts (Allium cepa L.) with cacao oleum as the basis. Examination of the physical quality of the preparation, namely homogeneity, organoleptic, pH, skin irritation, effectiveness as a lip moisturizer for 4 weeks. The results of the study showed that all the preparations produced met the requirements. Preparation with formulation 4 has the best quality using red onion extract (0.5 g), propylene glycol (0.5 g), cera alba (2.2 g), castor oil (1.5 g), tween 80 (0 .2 g), nipagin (0.02 g), BHT (0.005 g), oleum cacao (10 g) with a pH parameter test of 5.875; water content of 86.82%; orgnoleptic with acceptable color, odor and shape; homogeneity of 100%; and does not cause irritation.